Accuracy of magnetic resonance cholangiopancreaticography in the diagnosis of benign and malignant cause of obstructive jaundice - Temba Sherpa, Ngawang; Manandhar, Sagun; Karki, Anil; Karki, Prabhat (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Obstructive jaundice is one of the most common hepatobiliary diseases. Though USG is very good screening and diagnostic tool for obstructive jaundice its role is limited in gaseous abdomen, recent meal and patient’s body habitus. ERCP has very high accuracy in diagnosis of biliary disease especially choledocholithiasis and CBD stricture. Since ERCP is minimal invasive procedure with certain morbidity and mortality risk MRCP is standard technique for overall assessment of obstructive jaundice. This study aims to compare diagnostic accuracy of MRCP in diagnosing benign and malignant cause of obstructive jaundice taking HPE and ERCP as Gold standard.Method: This was a retrospective study reviewing MRCP findings of clinically diagnosed obstructive jaundice from 2018 to2021 at Patan Hospital, Kathmandu Nepal. Study was conducted after ethical clearance of the institutional review committee.Result: Among 66 patient Sensitivity, Specificity, PPV and NPV of MRCP for biliary obstruction due to malignant pathology were 89.50%, 93.60%, 85.00% and 95.70% respectively. Similarly for benign etiology, Sensitivity, Specificity, PPV and NPV accounted for 93.60%, 89.50%, 95.70% and 85.00% respectively. The overall diagnostic accuracy was 92.40%. Choledocholithiasis  was the most common benign cause of obstructive jaundice 31 (46.97%) cases, while periampullary carcinoma was the most common malignant cause eight (12.12%).Conclusion: MRCP is highly sensitive and specific test in the evaluation of benign and malignant biliary pathology. Being noninvasive and can have good diagnostic value despite use of contrast. So minimally invasive procedure ERCP can be reserved for therapeutic or diagnostic biopsy purpose only.